Bentuk Dan Pola Penyelesaian Sengketa Harta Bersama Di Indonesia - Mahmudah; Ramdani Wahyu Sururie (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
Abstract Joint property disputes in Indonesian society can be said to have never subsided and even tend to increase as the divorce rate continues to increase, the purpose of this research is to find out the pattern and form of settlement of joint property disputes.The development of the dynamics of law in Indonesia has experienced significant developments. This study discusses three things: the pattern of dispute resolution, the factors that lead to disputes, in the settlement of joint property disputes in Indonesia. This research is an analytical descriptive research which includes data collection methods, data compilation, and final data analysis. The findings of the study show that first, the meaning and limits of joint property as stated in Law no. 1 of 1974 and in the KHI can no longer be criminalized in the case of joint property itself. Settlement of joint property disputes in Indonesia through two settlement channels. Second, Law No. 1 of 1974 in principle has provided preventive measures so that there is no mixing of joint assets with innate assets. Third, the settlement of joint property disputes in Indonesia through two settlement channels, the first through litigation and the second through non-litigation. Fourth, the settlement of joint property disputes carried out in two ways, litigation and non-litigation, provides different dispute resolution models and different finding. Abstrak Sengketa harta bersama dalam masyarakat Indonesia dapat dikatakan tidak pernah surut bahkan cenderung meningkat seiring dengan angka perceraian yang terus meningkat, tujuan dari penelitian ini adalah untuk mengetahui pola dan bentuk penyelesaian sengketa harta bersama. Dinamika hukum di Indonesia telah mengalami perkembangan yang signifikan. Penelitian ini membahas tiga hal yaitu pola penyelesaian sengketa, faktor-faktor yang menimbulkan sengketa, dalam penyelesaian sengketa harta bersama di Indonesia. Penelitian ini merupakan penelitian deskriptif analitik yang meliputi metode pengumpulan data, penyusunan data, dan analisis data akhir. Hasil penelitian menunjukkan bahwa pertama, pengertian dan batasan harta bersama sebagaimana diatur dalam UU No. 1 Tahun 1974 dan dalam KHI tidak dapat lagi dipidana dalam perkara harta bersama itu sendiri. Penyelesaian sengketa harta bersama di Indonesia melalui dua jalur penyelesaian. Kedua, Undang-Undang Nomor 1 Tahun 1974 pada prinsipnya telah memberikan tindakan pencegahan agar tidak tercampurnya harta bersama dengan harta bawaan. Ketiga, penyelesaian sengketa harta bersama di Indonesia melalui dua jalur penyelesaian, yang pertama melalui jalur litigasi dan yang kedua melalui jalur nonlitigasi. Keempat, penyelesaian sengketa harta bersama yang dilakukan dengan dua cara, litigasi dan nonlitigasi, memberikan model penyelesaian sengketa yang berbeda dan temuan yang berbeda pula.